Low molecular weight-PAHs induced inflammation in A549 cells by activating PI3K/AKT and NF-κB signaling pathways. Issue 1 (25th January 2021) - Guo, Huizhen; Huang, Yushan; Wang, Huiling; Zhang, Zhewen; Li, Chengyun; Hu, Fengjing; Zhang, Wenwen; Liu, Yang; Zeng, Yong; Wang, Junling
Abstract: Our previous study has demonstrated that two low molecular weight-polycyclic aromatic hydrocarbons (LMW-PAHs), phenanthrene (Phe) and fluorene (Flu), alone and as a mixture could induce oxidative damage and inflammation in A549 cells. However, the associated mechanisms have not been well discussed. The aim of this study was to further investigate the roles of PI3K/AKT and NF-κB signaling pathways in the inflammatory effects in A549 cells induced by Phe, Flu and their mixture. The results indicated that Phe, Flu and their mixture significantly activated PI3K/AKT and NF-κB signaling pathways by increasing the phosphorylation levels of PI3K, AKT, IκBα and NF-κB p65. In addition, pro-inflammatory cytokine expressions of TNF-α and IL-6 induced by the binary mixture of Phe and Flu were all alleviated by co-treatment with PI3K/AKT and NF-κB specific inhibitors (LY294002 and BAY11-7082). The results suggested that PI3K/AKT and NF-κB signaling pathways played an important role in LMW-PAHs induced inflammation in A549 cells.